THE USE OF INFORMATION TECHNOLOGY INDUSTRY 4.0 "INTERNET OF THINGS" IN E-COMMERCE - Kis, Halyna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2020)
The purpose of the study is to analyze the features of the use of information technologies in industry 4.0 "Internet of Things" in e-commerce. The study hypothesizes that the use of Industry 4.0 technologies contributes to the development of modern marketing, data analysis and ensures the security of transactions between consumers on online platforms, which is a driver for the creation of innovative business models, which, in turn, ensure the effective development of business and e-commerce. The study determined that IoT technologies, big data and analytical capabilities have become an integral part of the development of retail at the present stage. With technological advances in a consumer-centric economic system, market participants can interact with customers through more diverse and effective means. In addition, businesses in the economic system can also optimize their operations and management, allocate and efficiently use resources based on consumer demand and quickly and accurately meet the desired demand by offering optimal goods and services. It is concluded that, as drivers of continuous innovation and transformation of the retail industry, enterprises should consider the technological innovations of Industry 4.0 with an open mind and actively apply them in their strategic transformations. That being said, it is very important to invest in marketing as well as research and innovation in order to achieve faster growth and a more solid position in the e-commerce market. Modern business models of e-commerce with using Industry 4.0 technologies that contribute to the development of modern marketing, data analysis and secure relationships between consumers on online platforms are identified. Industry 4.0 technologies drive the creation of innovative business models that enable the development of business.